An Analysis Structural Metaphor in Imagine Dragon's Selected Songs - Putu Nur Ayomi; Desak Putu Eka Pratiwi; Bamagin Fatwansyah (Riviera Publishing, 2022)
Introduction: Language is one of the most important parts of our life that is used every day. This is because language supports human communication. Communication is important because it reduces the level of ambiguity in social interaction. Purpose: This article aims to explore the use of Structural Metaphors in selected songs by rock band Imagine Dragon and their meanings. The theory used is from Lakoff, which is used to identify Structural Metaphors and the theory of meaning from Leeches. In this article, Method: the method used is a qualitative method to describe the meaning of structural metaphors comprehensively. Results: After analyzing the data, it was found that for each song such as Believer, Bad Liar, and Enemy, some lyrics contain structural metaphors based on the metaphor theory, but there are only five types of meaning out of seven types of meaning by Leech. The meanings found are Conceptual, Connotative, Collocative, Affective, and Thematic meanings. Conclusion: Based on the data, the analysis of Structural metaphor found in each lyric from selected songs by Imagine Dragon, the writer classified the meaning based on the song using the seven types of meaning.